1988
DOI: 10.1088/0031-8949/38/3/015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the interface on the crystallization of amorphous Ge in Pb/Ge multilayers

Abstract: The amorphous to crystalline phase transition of Ge in contact with Pb has been extensively investigated in Pb/Ge multilayers. We find that the Ge crystallizes at reduced temperatures in the range of 100 -200 °C depending on the thickness of the Ge and the Pb. Simultaneously the texture of tfie Pb improves and the layered structure completely disappears. The basis for the reduction of the crystallization temperature is the enhanced diffusion kinetics at the interface, caused by the adjacent Pb layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…With c;l and c;l equal to zero, equation (6) reduces to the step model, whereas for c;' and cdl tending to infinity, it gives the incoherent scattering intensity from M crystalline layers each consisting of hi planes. With c;' = 0, equation (6) reduces to equation ( 5 ) of [9].…”
Section: N= --Rmentioning
confidence: 99%
See 2 more Smart Citations
“…With c;l and c;l equal to zero, equation (6) reduces to the step model, whereas for c;' and cdl tending to infinity, it gives the incoherent scattering intensity from M crystalline layers each consisting of hi planes. With c;' = 0, equation (6) reduces to equation ( 5 ) of [9].…”
Section: N= --Rmentioning
confidence: 99%
“…The details of the structure of the individual components and the interface are often crucial for the understanding of the superconducting [2] and magnetic [3] properties of the multilayers. It has also been shown that the structure of the interface plays a dominant role in the melting [4] or crystallisation [5] behaviour of one of the components. Among various methods of characterising these composite materials, x-ray diffraction techniques are most often used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation